Mechanisms of Anterior Cruciate Ligament Injury and the Impact of Integrated Neuromuscular Training on Rehabilitation - Guangyao Ye (Ilmu Inovasi Nusantara, 2025)
The anterior cruciate ligament (ACL) plays a vital role in maintaining anterior stability of the knee joint. ACL injuries are among the most common cases in sports medicine and often result in significant impairment of athletic performance and overall quality of life. Such injuries not only cause knee dysfunction but also increase the long-term risk of complications such as osteoarthritis. The mechanisms of injury are influenced by anatomical factors, high-risk movement patterns, and deficits in neuromuscular control, making ACL rehabilitation a crucial issue in both medical and athletic fields. This study aims to provide a comprehensive examination of ACL injury mechanisms and to evaluate the effectiveness of Integrated Neuromuscular Training (INT) as a rehabilitation strategy. INT, rooted in neuromuscular control principles, is designed to restore knee and lower-limb function more effectively through a systematic and multidimensional approach. The methodology of this study is based on a literature review and theoretical analysis of prior research addressing ACL injury mechanisms, rehabilitation interventions, and the clinical as well as athletic application of INT. The findings indicate that INT is effective in enhancing knee joint stability, correcting faulty movement patterns, and reducing the risk of re-injury. Furthermore, INT contributes to improved functional performance and accelerates recovery in athletes undergoing ACL rehabilitation. The implications of this study suggest that INT can be applied not only in clinical rehabilitation settings but also in preventive training programs for athletes at high risk of ACL injury. The study provides theoretical insights for refining exercise intervention frameworks and offers practical guidance for clinicians and sports practitioners in both injury prevention and treatment